Toward Gender-Informed Energy Subsidy Reforms : Findings from Qualitative Studies in Europe and Central Asia - World Bank (Washington, DC, 2015)
Since the 1990s, most states in Europe and Central Asia (ECA) have embarked on energy sector reforms. These have included removing subsidies, which has resulted in increased end-user costs for energy. The research presented here comprises an integral part of a set of qualitative studies on poverty and social impacts of energy subsidy reforms. In particular, it examines what it means for energy subsidy reforms to be more gender sensitive. The purpose of this research is to illustrate the extent to which energy subsidy reforms in the ECA region differently impact men and women. Prior global studies on gender and energy suggest that men and women have different priorities when it comes to energy use; that the reforms may have unequal effects on their well-being; that they face different challenges in interacting with energy providers or social assistance institutions; and may have different views on and knowledge of policy reforms. The target audience for this study is development practitioners, public officials, and civil society actors involved in social sustainability and the communications aspects of energy reform policies.